The Development of a Novel Broad-Spectrum Influenza Polypeptide Vaccine Based on Multi-Epitope Tandem Sequences - Song Zhao; Junhao Luo; Wenhui Guo; Li Li; Siyu Pu; Libo Dong; Wenfei Zhu; Rongbao Gao (Vaccines)
Background: Polypeptide vaccines have the potential to improve immune responses by targeting conserved and weakly immunogenic regions in antigens. This study aimed to identify and evaluate the efficacy of a novel influenza universal vaccine candidate consisting of multiple polypeptides derived from highly conserved regions of influenza virus proteins hemagglutinin (HA), neuraminidase (NA), and matrix protein 2 (M2). Methods: Immunoinformatics tools were used to screen conserved epitopes from different influenza virus subtypes (H1N1, H3N2, H5N1, H7N9, H9N2, and IBV). A polypeptide vaccine, P125-H, was constructed by linking multiple epitopes using Ii-Key technology. The immunogenicity of P125-H was assessed in mice using MF59-adjuvanted P125-H via intraperitoneal injection. Hemagglutination inhibition (HI) and neutralizing antibody responses were measured, along with IFN-γ levels in spleen lymphocytes. Protective efficacy was evaluated using viral challenge with lethal doses of H1N1 and H7N9. Results: Mice immunized with P125-H generated high levels of HI and neutralizing antibodies against multiple influenza strains. IFN-γ production was significantly elevated in spleen lymphocytes upon stimulation with the vaccine. P125-H protected mice from influenza infection, reducing weight loss and the viral load in the lungs, mitigating lung pathology, and decreasing mortality. Conclusions: The P125-H vaccine induced broad cross-protection against multiple influenza strains and elicited robust immune responses. It demonstrates strong potential as a candidate for a universal influenza vaccine.